Queenstown Association (U.S.) records - Queenstown Association (U.S.)
Correspondence, minutes, membership lists, pamphlets, newspaper clippings, photographs, and other papers, relating chiefly to the association's social activities. Primarily the files of founder and secretary-treasurer, Junius Spencer Morgan. Includes a typewritten transcript of Morgan's diary (1917-1918). Correspondents include Lewis Bayly, Robert Bostwick Carney, Arthur S. Carpender, Arthur Philip Fairfield, Langhorne Gibson, William Frederick Halsey, Arthur J. Hepburn, Alfred Wilkinson Johnson, Samuel Eliot Morison, Joel Roberts Poinsett Pringle, William Sowden Sims, and Joseph K. Taussig.
Association of commissioned officers of the United States Navy who were stationed at the naval base in Queenstown, Ireland, during World War I. Established, 1921; disbanded, 1961.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: Bayly, Lewis, -- 1857-1938 -- Correspondence; Carney, Robert Bostwick, -- 1895-1990 -- Correspondence; Carpender, Arthur S. -- 1884-1960 -- Correspondence; Fairfield, Arthur Philip, -- 1877-1946 -- Correspondence; Gibson, Langhorne, -- 1899- -- Correspondence; Halsey, William Frederick, -- 1882-1959 -- Correspondence; Hepburn, Arthur J. -- 1877-1964 -- Correspondence; Johnson, Alfred Wilkinson, -- 1876-1963 -- Correspondence; Morgan, Junius Spencer, -- 1892-1960.; Morison, Samuel Eliot, -- 1887-1976 -- Correspondence; Pringle, Joel Roberts Poinsett, -- 1873-1932 -- Correspondence; Sims, William Sowden, -- 1858-1936 -- Correspondence; Taussig, Joseph K. -- 1877-1947 -- Correspondence; United States. -- Navy -- Officers; Navy-yards and naval stations -- Ireland -- Queenstown; World War, 1914-1918 -- United States -- Societies, etc